SEKOLAH RAMAH ANAK, DISIPLIN, DAN BUDAYA KEKERASAN DI SEKOLAH DI INDONESIA - Khaerul Umam Noer; AbdulAziz Hanafi; Dhea Ariesta Khairunnisa; Fairus Dwi Putri (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Since 2014 Indonesia has entered a new phase in the efforts to fulfill children's rights, especially the protection of children in schools through Child-Friendly Schools (CFS). Until May 2019, there were 16,880 CFS’s throughout Indonesia. There are six indicators of CFS, this paper focus on how the the application of discipline without violence in school. Using a mixed research method, through a survey of 3272 students in 75 schools in Bekasi, Depok and Bandung, and interviews with the students, principal and school committee. This research shows that the CFS policy in schools is still not running well. Violence, in the name of discipline, still continues at school. Students are still physically punished, there is no mechanism for the conversion of sentences to assignments, so there is no mechanism for complaints and prosecution of sexual harassment cases. This is certainly worrying, because CFS policy is not just a school claim, but must manifest in school policy and implementation.